Development and Evaluation of Ethosomes Loaded with Zingiber zerumbet Linn Rhizome Extract for Antifungal Skin Infection in Deep Layer Skin - Kampanart Huanbutta; Napapat Rattanachitthawat; Kunlathida Luangpraditkun; Pornsak Sriamornsak; Vivek Puri; Inderbir Singh; Tanikan Sangnim (MDPI AG, 2022)
Skin fungal infection is still a serious public health problem due to the high number of cases. Even though medicines are available for this disease, drug resistance among patients has increased. Moreover, access to medicine is restricted in some areas. One of the therapeutic options is herbal medicine. This study aims to develop an ethosome formulation loaded with Zingiber zerumbet (L.) Smith. rhizome extract for enhanced antifungal activity in deep layer skin, which is difficult to cure. Ethosomes were successfully prepared by the cold method, and the optimized formulation was composed of 1% (w/v) phosphatidylcholine and 40% (v/v) ethanol. Transmission electron microscope (TEM) images revealed that the ethosomes had a vesicle shape with a diameter of 205.6-368.5 nm. The entrapment of ethosomes was 31.58% and could inhibit the growth of Candida albicans at a concentration of 312.5 μg/mL. Finally, the ethosome system significantly enhanced the skin penetration and retention of the active compound (zerumbone) compared with the liquid extract. This study showed that Z. zerumbet (L.) rhizome extract could be loaded into ethosomes. The findings could be carried over to the next step for clinical application by conducting further in vivo penetration and permeation tests.